2013
DOI: 10.3329/ijarit.v1i1-2.13936
|View full text |Cite
|
Sign up to set email alerts
|

Study of Shoot Multiplication of Strawberry (Fragaria ananassa)

Abstract: Effects of different hormonal concentration on multiple shoot formation of RABI Strawberry-3 were studied. Where the explants were runner tips that cultured on MS basal medium supplemented with 6-Benzyl Adenine and Kinetin. The maximum percentage 80% of shoot was obtained from Benzyl Adenine concentrations of 0.5 mg/l and 1.0 mg/l whereas Kinetin concentrations were 1.5 mg/l and 2.0 mg/l separately. More promising result was found by combining two impressive concentrations of each hormone. When MS basal media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…The presented results were in accordance with the results of Zobayer et al, 2011 andElKichaoui (2014) who found that the best BA concentrations for multiplication in strawberry are 0.5 and 1 mg/l. Also, El-Sayed et al (2017) found that BA concentration at 0.5 mg/l was more effective for shoot multiplication in cv.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The presented results were in accordance with the results of Zobayer et al, 2011 andElKichaoui (2014) who found that the best BA concentrations for multiplication in strawberry are 0.5 and 1 mg/l. Also, El-Sayed et al (2017) found that BA concentration at 0.5 mg/l was more effective for shoot multiplication in cv.…”
Section: Resultssupporting
confidence: 92%
“…Our results were in the same direction with those obtained by El-Sayed et al (2017) who found that the 6 th subcultures and the BA concentration up to 0.5 mg/l were the best for multiplication rate in three strawberry cultivars, namely "Camarosa", "Festival" and "Sweet Charlie". Also, the results of Zobayer et al, 2011 proved that the best BA concentration for high multiplication rate was 0.5 mg/l as reported by our results.…”
Section: Resultssupporting
confidence: 87%
“…Hasan et al (2010) found highest number of usable shoot at the concentration of 1.0 mgL -1 BA with 0.1 mgL -1 NAA. Zobayer et al (2011) obtained the maximum shoots of RABI Strawberry-3 from 0.5 mgL -1 BA + 1.0 mgL -1 . Sakila et al (2007) showed that nodal segments of strawberry gave rise to multiple shoots when cultured on MS medium supplemented with different concentration of BA with KIN or GA3 and the highest response of shoot multiplication was obtained in MS containing 1.5 mgL -1 BA + 0.5 mgL -1 KIN.…”
Section: Effect Of Growth Regulators On Shoot Multiplication and Shoot Lengthmentioning
confidence: 90%